The effect of leptin on utero-placental expression of EPHB4, Ephrin-B1, Ephrin-B2 and blood pressure in Sprague Dawley Rats / Norizan Kamal Basah - Kamal Basah, Norizan (2017)
Background: Ephs and ephrins might play a role in the migration of cytotrophoblast during endometrial invasion. Objective: This study attempts to establish the pattern of expression of EPHB4, Ephrin-B1 and Ephrin-B2 in the utero-placental unit during pregnancy in control and leptin-treated rats. Method: Normotensive female Sprague Dawley rats, aged 12 weeks in pro-estrous were individually housed overnight with a male. Upon confirmation of mating the rats were randomized into two groups; control group and leptin-treated group. These groups were further divided into 10 subgroups (n=6 per group). Rats in the leptin-treated groups were given daily 60 µg/kg BW/day of leptin subcutaneously from two weeks prior to mating and until the day they were euthanized. Rats were euthanized every 2 days from day 5 of pregnancy and the placentae were collected for RT-PCR and immunohistochemistry. Data were analyzed using two-way ANOVA and expressed as mean ± SEM. Result: Results showed that Ephrin-B1 and EPHB4 expressions in the placenta and uterus decreased significantly from early to mid-pregnancy and then increased towards the end of pregnancy in normal rats (p<0.001). Ephrin-B2 expression decreased over the course of pregnancy in both the placenta and uterus (p<0.001). Ephrin-B1 expression was significantly higher in the leptin-treated group at day 21 of pregnancy. It appears that Ephrins-B1, B2 and EPHB4 are expressed by both the placenta and the uterus of the rat and their expression varies along the course of pregnancy. Conclusion: In conclusion, although the expression of Ephrin-B1 is affected by leptin, it might not have a role in leptin induced hypertension during pregnancy in the rats.